Avaliação da liberdade rotacional e desajuste vertical da conexão implante/pilar de hexágono externo e interno após simulação de torques de inserção - Cabrera, Alberto Eduardo Bullen (2011)
The implant-abutment connection has to ensure an accurate alignment and as many as repositioning needed during the prostheses installation. Objectives: The purpose of this study was to evaluate- the rotational freedom (between implants and their corresponding abutments) after applying different surgical insertion torques. Methods: Twenty conventional, 20 internal grip external hex implants and 20 internal hexagonal AMP CM implants (/P-i Brånemark Philosophy/Bauru/Brazil) were secured to a base in degree scale device. The minimum degree was 0.5. The mounts were screwed to the conventional implants using a manual torque wrench (7Ncm). Then, the mounts/key-grips were fit to implants and insertion torque forces (0/30/40/60/80Ncm) were applied during 60s. After, removing the mount/key grip of the implants, the abutments were placed and the rotational freedom was measured. All procedures were repeated three times/different positioning for each implant. Data were subjected to ANOVA and T-test. Mean values and standard deviations were recorded. Results: The rotational freedom was statistically different among all torque forces (ANOVA/Tukey p<0.05) for conventional implants. The internal grip implants showed a statistically significant difference between torque forces 0NCm/40NCm and 40NCm/80NCm (ANOVA/Tukey p<0.01). The internal hexagonal implant showed a statistically significant difference between torque forces 0Ncm/40Ncm, 0Ncm/60Ncm and 30Ncm/60Ncm (ANOVA/Tukey p<0.0001). Statistically significant diferences were found comparing the rotational freedom between conventional/internal grip implants for torque: 30/40/60/80NCm (T-test p<0.01). All internal grip hex implants and internal hexagonal implants AMP CM showed rotational freedom less or equal to 4 degrees, independently of torque. All the conventional hex implants submitted to 0/30/40NCm torque obtained rotational freedom below or equal to 5 degrees and all the implants submitted to 60/80NCm were between 5 and 9 degrees. Conclusions: The Ti grade 2 implants tested showed an increase in the rotational freedom as increased the surgical insertion torque mainly in the conventional hex implants. The conventional implants showed higher rotational freedom than internal grip hex implants and the internal hexagonal implants for the same torque forces.